Modeling of the Gamma-Glutamyl Carboxylase Reaction - Lyons, Zoe; Reinhardt, Clorice (My University, 2015)
The purpose of this study was to discuss the results of this computation study about modeling the gamma-glutamyl carboxylase reaction, which is responsible for clotting factors in the blood.
Color poster with text and images.
Keywords: Density functional theory; Chemistry; Gamma-glutamyl carboxylase; Posters